2015
DOI: 10.1007/s10840-015-0085-2
|View full text |Cite
|
Sign up to set email alerts
|

Mobile thrombus on cardiac implantable electronic device leads of patients undergoing cardiac ablation: incidence, management, and outcomes

Abstract: Purpose The rates of cardiovascular implantable electronic device (CIED) implantations and cardiac ablation procedures are increasing worldwide. To date, the management of CIED lead thrombi in the periablation period remains undefined and key clinical management questions remained unanswered. We sought to describe the clinical course and management strategies of patients with a CIED lead thrombus detected in the periablative setting. Methods We performed a retrospective analysis of all patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…With the use of TEE the incidence of AMEL increased to 28% (Downey et al, 2011; Dundar et al, 2011; Golzio et al, 2019; Lo et al, 2006). Intracardiac echocardiography during ablation procedures revealed incidental masses on the leads in 30% of patients (Dundar et al, 2011; Sugrue et al, 2016). In the present study, AMEL were found in 58.7% of patients undergoing TLE.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of TEE the incidence of AMEL increased to 28% (Downey et al, 2011; Dundar et al, 2011; Golzio et al, 2019; Lo et al, 2006). Intracardiac echocardiography during ablation procedures revealed incidental masses on the leads in 30% of patients (Dundar et al, 2011; Sugrue et al, 2016). In the present study, AMEL were found in 58.7% of patients undergoing TLE.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of LBE in this clinical context was historically felt to be proof of endocarditis. However, there are numerous studies demonstrating that LBEs can often be present without any evidence of infection 10–13 . The optimal management of these findings, which are often incidental, needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 8 , 9 However, there is growing evidence that not all LBEs seen on TEE are suggestive of CIED infections, particularly when the TEE study was obtained for noninfectious indications. 10 , 11 , 12 , 13 We sought to evaluate patients who underwent TEE and had an indwelling CIED; detailed imaging review and chart review was conducted to determine if there were differences in clinical and echocardiographic features in patients with noninfectious versus infectious LBEs.…”
Section: Introductionmentioning
confidence: 99%
“…Another important TEE finding that deserves attention after TLE is dislodgement of vegetations and residual fibrosis. Previous research in preoperative TTE, TEE and ICE has found movable masses attached to the leads, representing vegetations or connective tissue both in asymptomatic and symptomatic patients (30)(31)(32)(33)(34). Some of them may remain in cardiac cavities after TLE whereas others may emerge during lead dissection.…”
Section: Discussionmentioning
confidence: 99%